2019
DOI: 10.1007/s00134-019-05647-5
|View full text |Cite
|
Sign up to set email alerts
|

Key mechanisms by which post-ICU activities can improve in-ICU care: results of the international THRIVE collaboratives

Abstract: Objective To identify the key mechanisms that clinicians perceive improve care in the intensive care unit (ICU), as a result of their involvement in post-ICU programs. Methods Qualitative inquiry via focus groups and interviews with members of the Society of Critical Care Medicine’s THRIVE collaborative sites (follow-up clinics and peer support). Framework analysis was used to synthesize and interpret the data. Results Five key mechanisms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…Post-ICU recovery programs staffed by a team of providers (ie, pulmonologists, intensivists, pharmacists, advanced practice providers, nurses, physical and occupational therapists, respiratory therapists, social workers, case managers, and mental health providers) can diagnose and treat PICS impairments. [228][229][230] These clinics also facilitate access to necessary subspecialties (tables 3, 4). The comprehensive approach of post-ICU clinics mirror the magnitude that critical illness affects multiple domains of a patient's health.…”
Section: Post-acute Covid-19 Complicationsmentioning
confidence: 99%
“…Post-ICU recovery programs staffed by a team of providers (ie, pulmonologists, intensivists, pharmacists, advanced practice providers, nurses, physical and occupational therapists, respiratory therapists, social workers, case managers, and mental health providers) can diagnose and treat PICS impairments. [228][229][230] These clinics also facilitate access to necessary subspecialties (tables 3, 4). The comprehensive approach of post-ICU clinics mirror the magnitude that critical illness affects multiple domains of a patient's health.…”
Section: Post-acute Covid-19 Complicationsmentioning
confidence: 99%
“…Our findings suggest that many patients and families need help and support beyond traditional medical follow-up after an ICU admission, which is supported in work by others. 23 We found that participants may have difficulty adjusting to a 'new normal' and possibly lack resilience. Their ICU experience appears to shape the feelings they have about both the critical illness and their transition back to a 'normal life', consistent with other narrative studies in ICU populations.…”
Section: Discussionmentioning
confidence: 74%
“…Similar to findings from this study, a study by Maley et al (2016) identified ongoing physical impairments, mental health issues, and difficulties in scheduling and coordinating follow-up appointments as major barriers faced by survivors. While other studies have addressed financial barriers to establishing post-ICU clinics (Haines et al, 2019), the current study identified personal financial barriers, including participants not being able to have the necessary follow-up procedures and care post-hospital discharge due to lack of insurance and money. Healthcare providers need to be aware of barriers that survivors experience after they are discharged to assist in overcoming these barriers.…”
Section: Discussionmentioning
confidence: 99%